The Effect Of Variations In Extensive Interval Training On Aerobic Endurance Fighter Muaythai Fightculture Medan - Tumangger, Verianto; Siahaan, David (Journal Coaching Education Sports, 2022)
This study aims to determine the Effect of Extensive Interval Training Variations on the Endurance of the Aerobic Fighter Muaythai FightCulture Medan 2021. This research was carried out in the UNIMED Multi-Purpose Field. The population in this study were Fighter Muaythai Fightculture and the sampling technique used a total sampling technique of 5 Muaythai athletes. The research method used was experimental method (treatment) with data collection techniques involving one independent variable and one dependent variable, namely Extensive Interval Training Variation as the independent variable and Aerobic Endurance as the dependent variable. The results of hypothesis testing showed that the probability value (Asymp. Sig) was 0.043 < significant level 0.05 (Asymp. Sig. (2-tailed) 0.043 < 0.05). The conclusion of the study is that there is a significant effect of Extensive Interval training on improving the 2021 Muaythai Medan Fighter Fightculture.